2016
DOI: 10.7554/elife.13764
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of visual, parietal, and frontal motor cortices in memory-guided sensorimotor decisions

Abstract: Mapping specific sensory features to future motor actions is a crucial capability of mammalian nervous systems. We investigated the role of visual (V1), posterior parietal (PPC), and frontal motor (fMC) cortices for sensorimotor mapping in mice during performance of a memory-guided visual discrimination task. Large-scale calcium imaging revealed that V1, PPC, and fMC neurons exhibited heterogeneous responses spanning all task epochs (stimulus, delay, response). Population analyses demonstrated unique encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
270
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(319 citation statements)
references
References 81 publications
(167 reference statements)
28
270
8
Order By: Relevance
“…Similar results were obtained weeks after the mouse achieved plateau performance, suggesting that PPC activity was necessary for performing the task even in the post-learning phase. These results were consistent with our earlier pharmacological inactivation experiments and other studies showing a role for rodent PPC in visual decision tasks (Goard et al, 2016; Harvey et al, 2012; Licata et al, 2017; Raposo et al, 2014). We note that although inactivation was centered on PPC, such activity manipulations may have effects that spread beyond PPC (Otchy et al, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained weeks after the mouse achieved plateau performance, suggesting that PPC activity was necessary for performing the task even in the post-learning phase. These results were consistent with our earlier pharmacological inactivation experiments and other studies showing a role for rodent PPC in visual decision tasks (Goard et al, 2016; Harvey et al, 2012; Licata et al, 2017; Raposo et al, 2014). We note that although inactivation was centered on PPC, such activity manipulations may have effects that spread beyond PPC (Otchy et al, 2015).…”
Section: Resultssupporting
confidence: 93%
“…Also, because PPC activity was not required during the delay period, it seems unlikely that PPC had an essential short-term memory of the cue or upcoming action. Collectively the results here and from previous work support the hypothesis that PPC functions in the visual-to-motor transformation (Goard et al, 2016; Harvey et al, 2012; Licata et al, 2017; Raposo et al, 2014). This hypothesis is consistent with PPC’s connectivity in which it receives multisensory input, has recurrent connections with frontal regions, and has outputs to motor-related structures (Harvey et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…As this may indicate, the translation from action potentials in the motor cortex to the flexion of muscles is a very complex problem that has so far escaped widely accepted and principled explanations. However, the fundamental findings in primates have been replicated in rodents, including, for example, the presence of preparatory activity prior to movement (Murakami et al 2014, Storozhuk et al 1984) and its importance in memory-guided behavior (Goard et al 2016, Guo et al 2014), the predominance of activity during phasic as opposed to tonic muscle contractions (Zhuravin & Bures 1989), and the temporal complexity of activity throughout movement (Hyland 1998). More recently, rodents have allowed for more targeted investigations of activity by fine-scale spatial organization, layer, and cell type, paving the way for a more circuit-oriented view of motor cortex activity (Dombeck et al 2009, Hira et al 2013a, Isomura et al 2009, Li et al 2015, Tsubo et al 2013).…”
Section: Functional Plasticitymentioning
confidence: 99%
“…Another body of experiments, performed both in primates and in rodents, indicated a role of PPC in decision making, especially for decisions based on vision (Andersen and Cui, 2009;Erlich et al, 2015;Goard et al, 2016;Gold and Shadlen, 2007;Katz et al, 2016;Latimer et al, 2015;Licata et al, 2017;Platt and Glimcher, 1999;Raposo et al, 2014;Sugrue et al, 2004). Studies in rodents found decision signals to be widespread in PPC populations, where they are mixed with other signals (Goard et al, 2016;Raposo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rodents found decision signals to be widespread in PPC populations, where they are mixed with other signals (Goard et al, 2016;Raposo et al, 2014). One study, in particular, found decision signals to be remarkably common: each PPC neuron fires only for a particular decision and only at a particular moment in a stereotyped sequence (Harvey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%